O ensino superior de contabilidade: uma análise qualitativa a partir da fala de professores - Madeira, Geova Jose (1990)
In this research the author tries to discuss the Accountancy teaching at the University level in Brazil. trying to know the professors opinion about questions related to this subject. Initially the author looked for the bibliography intending to know better the Educational Brazilian system, highlighting the Accountancy teaching through old and new papers. The data collection was done through and interview with open questions. With this method it was possible to do a critical analyzing the professors speech. The author concludes that the professors opinion supported most of the questions showed in the bibliography concerning to the Accountancy teaching quality. And he states that to make the Accountancy teaching better it is important to improve training courses for the professors and to review the curriculum of the Accountancy course.